Investor’s Mood at ASIAN Games Event - Devy, Happy Sista; Irawan, Bahrain Pasha (Universitas Islam Negeri Sunan Kudus, 2019)
Goals of the research to analyze whether occurred abnormal return of ASIAN Games phenomena and see how investors react to the big ASIAN Games 2018 event in Indonesia. . This reseach uses a sample of companies included in the hotel, restaurant and tourism sub-sector on the Indonesia Stock Exchange (IDX) during the observation period, based on the purposive sampling method which obtained 22 companies and used the event study method. There is a significant abnormal return but not on the phenomenon of the Asian Games 2018. This shows that investors still wait and see to the organization of the Asian Games in 2018. No difference of abnormal return before and after the Asian Games 2018. This is because, as investors look to the many tourists who have started to flock to Indonesia before the Asian Games in 2018 took place.